1999
DOI: 10.1136/hrt.81.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction from paradoxical embolism in a case of massive pulmonary thromboembolism

Abstract: Objective-In the chronic phase of myocardial infarction, the relation between myocardial recovery and infarct related artery status remains unclear. The spontaneous changes in rest-redistribution thallium defect size were prospectively studied over six months in 52 patients with chronic Q wave myocardial infarction. Design-Changes in rest thallium defect size, thallium uptake in the infarct area, and radionuclide left ventricular ejection fraction were compared to the quantitative coronary angiogram data. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These reports also include cases deemed with air, tumor, and brain tissue embolization. [24][25][26][27][28][29][30][31][32] In 1988 Jungbluth et al identified 27 published cases of paradoxical coronary embolism, and 21 additional cases have been reported until 2004. 33,34 The unique subgroup particularly prone to experience paradoxical embolism comprises patients with PE and PFO.…”
Section: Paradoxical Embolism As a Probable Cause Of Acute Coronary Smentioning
confidence: 99%
“…These reports also include cases deemed with air, tumor, and brain tissue embolization. [24][25][26][27][28][29][30][31][32] In 1988 Jungbluth et al identified 27 published cases of paradoxical coronary embolism, and 21 additional cases have been reported until 2004. 33,34 The unique subgroup particularly prone to experience paradoxical embolism comprises patients with PE and PFO.…”
Section: Paradoxical Embolism As a Probable Cause Of Acute Coronary Smentioning
confidence: 99%
“…Additionally, pulmonary embolism, which already suggests the presence of venous thrombosis and causes an increase of the right heart pressure, enhancing right-to-left shunting in the presence of an interatrial connection, should raise the suspicion of paradoxical embolism when occuring simultaneously with systemic embolization. However, unless clear evidence is found, like a thrombus transiting from the right to the left atrium, it is often difficult to ascribe the occurence of a myocardial infarction to paradoxical thromboembolism [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…3 Pulmonary embolism (or any condition that raises right atrial pressure) is frequently implicated in the increased right heart pressures that set the stage for right-to-left shunting via a PFO. 4,7,9 TEE is crucial for accurate diagnosis and appropriate management when paradoxical embolism is suspected. 10 TEE study with color Doppler and contrast echocardiography is the most sensitive diagnostic technique for diagnosing PFO.…”
Section: Discussionmentioning
confidence: 99%